Applying next generation sequencing to detect tick-pathogens in Dermacentor nuttalli, Ixodes persulcatus, and Hyalomma asiaticum collected from Mongolia - Graham A. Matulis; Jira Sakolvaree; Bazartseren Boldbaatar; Nora Cleary; Ratree Takhampunya; B. Katherine Poole-Smith; Abigail A. Lilak; Doniddemberel Altantogtokh; Nyamdorj Tsogbadrakh; Nitima Chanarat; Nittayaphon Youngdech; Erica J. Lindroth; et al. (Ticks and Tick-Borne Diseases, 2023)
Ticks and tick-borne diseases represent major threats to the public health of the Mongolian population, of which an estimated 26% live a traditional nomadic pastoralist lifestyle that puts them at increased risk for exposure. Ticks were collected by dragging and removal from livestock in Khentii, Selenge, Tuv, and Umnugovi aimags (provinces) during March-May 2020. Using next-generation sequencing (NGS) with confirmatory PCR and DNA sequencing, we sought to characterize the microbial species present in Dermacentor nuttalli (n = 98), Hyalomma asiaticum (n = 38), and Ixodes persulcatus (n = 72) tick pools. Rickettsia spp. were detected in 90.4% of tick pools, with Khentii, Selenge, and Tuv tick pools all having 100% pool positivity. Coxiella spp. were detected at an overall pool positivity rate of 60%, while Francisella spp. were detected in 20% of pools and Borrelia spp. detected in 13% of pools. Additional confirmatory testing for Rickettsia-positive pools demonstrated Rickettsia raoultii (n = 105), Candidatus Rickettsia tarasevichiae (n = 65) and R. slovaca/R. sibirica (n = 2), as well as the first report of Candidatus Rickettsia jingxinensis (n = 1) in Mongolia. For Coxiella spp. reads, most samples were identified as a Coxiella endosymbiont (n = 117), although Coxiella burnetii was detected in eight pools collected in Umnugovi. Borrelia species that were identified include Borrelia burgdorferi sensu lato (n = 3), B. garinii (n = 2), B. miyamotoi (n = 16), and B. afzelii (n = 3). All Francisella spp. reads were identified as Francisella endosymbiont species. Our findings emphasize the utility of NGS to provide baseline data across multiple tick-borne pathogen groups, which in turn can be used to inform health policy, determine regions for expanded surveillance, and guide risk mitigation strategies.